Improvement of Vehicle Stability Using Reinforcement Learning - Amaral, Janaína R.; Göllinger, Harald; Fiorentin, Thiago A. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2018)
This paper presents a preliminary study on the use of reinforcement learning to control the torque vectoring of a small rear wheel driven electric race car in order to improve vehicle handling and vehicle stability. The reinforcement learning algorithm used is Neural Fitted Q Iteration and the sampling of experiences is based on simulations of the vehicle behavior using the software CarMaker. The cost function is based on the position of the states on the phase-plane of sideslip angle and sideslip angular velocity. The resulting controller is able to improve the vehicle handling and stability with a significant reduction in vehicle sideslip angle.